An FMRFamide Neuropeptide in Cuttlefish Sepia pharaonis: Identification, Characterization, and Potential Function - Yang Zhu; Lian-lian Sun; Jun-hong Wu; Hui-hui Liu; Li-bing Zheng; Zhen-ming Lü; Chang-feng Chi (Molecules, 2020)
Neuropeptides are released by neurons that are involved in a wide range of brain functions, such as food intake, metabolism, reproduction, and learning and memory. A full-length cDNA sequence of an FMRFamide gene isolated from the cuttlefish Sepia pharaonis (designated as SpFMRFamide) was cloned. The predicted precursor protein contains one putative signal peptide and four FMRFamide-related peptides. Multiple amino acid and nucleotide sequence alignments showed that it shares 97% similarity with the precursor FMRFamides of Sepiella japonica and Sepia officinalis and shares 93% and 92% similarity with the SpFMRFamide gene of the two cuttlefish species, respectively. Moreover, the phylogenetic analysis also suggested that SpFMRFamide and FMRFamides from S. japonica and S. officinalis belong to the same sub-branch. Tissue expression analysis confirmed that SpFMRFamide was widely distributed among tissues and predominantly expressed in the brain at the three development stages. The combined effects of SpFMRFamide+SpGnRH and SpFLRFamide+SpGnRH showed a marked decrease in the level of the total proteins released in the CHO-K1 cells. This is the first report of SpFMRFamide in S. pharaonis and the results may contribute to future studies of neuropeptide evolution or may prove useful for the development of aquaculture methods for this cuttlefish species.